IMPLEMENTASI SISTEM MANAJEMEN MUTU ISO 9001:2015 PADA KUALITAS PESERTA DIDIK DI SMK PGRI 1 JOMBANG - Khoirur Roziqin, Muhamad; Prasetyo, Teguh (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
Students are individuals who participate in an educational program to develop their potential. School institutions play a crucial role in providing education for students. Vocational High School PGRI 1 Jombang is an institution that adheres to the SMM ISO 9001:2015 standard. The research aims to: 1) Understand the implementation of SMM ISO 9001:2015 at SMK PGRI 1 Jombang and its impact on the quality of students. 2) Identify the supporting and inhibiting factors in implementing QMS ISO 9001:2015 at SMK PGRI 1 Jombang. The research employed a qualitative methodology with a descriptive approach. The methods utilized by the researcher include: 1) Observation, 2) Interviews, 3) Documentation. The results of the research at SMK PGRI 1 Jombang indicate that: The implementation of SMM ISO 9001:2015 is proceeding effectively, thereby enhancing the institution's quality and positively influencing student outcomes. Supporting factors include parental involvement, policies governing the ISO 9001:2015 system, the New Student Admission System (PPDB), student readiness, collaboration with the business/industrial sector (DU/DI), and the implementation of learning outcomes assessments. Inhibiting factors encompass parental circumstances, policies related to the ISO 9001:2015 system, the New Student Admission System (PPDB), student readiness, collaboration with the business/industrial sector (DU/DI), and the execution of learning outcomes assessments.